Antidiabetic Effects of Aronia melanocarpa and Its Other Therapeutic Properties - Banjari, Ines; Misir, Andreja; Šavikin, Katarina; Jokić, Stela; Molnar, Maja; De Zoysa, H. K. S.; Waisundara, Viduranga Y. (Frontiers in Nutrition, 2017)
Diabetes is a global pandemic which warrants urgent attention due to its rising prevalence and economic burden. Thus, many alternative therapies are being researched for anti-diabetic properties, given the inefficacy of current medicinal treatments. From this perspective, Aronia melanocarpa or Black Chokeberry has been investigated for its therapeutic properties in many studies, especially for its ability to combat hyperglycemia-induced oxidative stress and the macrovascular complications of diabetes including cardiovascular disease. Though A. melanocarpa is native to the eastern areas of North America, it has been planted extensively in Europe and Asia as well. Several in vivo studies have displayed the antioxidant properties of A. melanocarpa berry juice and plant extract in rat models where oxidative stress markers were observed to have significant reductions. Some of the potent bioactive compounds present in the fruits and other parts of the plant were identified as (-)-epicatechin, chlorogenic acid, neochlorogenic acid and cyanidin-3-galactoside. Overall, A. melanocarpa could be considered a good source of antioxidants which is effective in combating hyperglycemia-induced oxidative stress.